2013
DOI: 10.1111/sji.12088
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of CD30 on CD3 T Lymphocytes in Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune systemic disease caused as a result of an imbalance of Th1-/Th2-type cytokines. The soluble form of CD30 (CD30s) released from peripheral blood cells has been described as a marker of active disease in Th2-type immune response as in SLE. However, the expression of CD30 on CD3 T lymphocytes from patients with SLE has not been studied yet. Therefore, we have addressed our study to attempt this issue, studying CD30 expression by flow cytometry on CD3 T lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Inflammation from EBV infection which has also been observed as a cause of the CD30 expression in bystander neoplastic cells and elevated soluble CD30 [ 14 ]. This description has been also supported by other studies investigating inflammatory disorders such as systemic lupus erythematosus and inflammatory bowel disease [ 17 , 18 ]. That might be why the effect of the CD30 expression is more obvious among studies included participants predominant in the early stage.…”
Section: Discussionsupporting
confidence: 81%
“…Inflammation from EBV infection which has also been observed as a cause of the CD30 expression in bystander neoplastic cells and elevated soluble CD30 [ 14 ]. This description has been also supported by other studies investigating inflammatory disorders such as systemic lupus erythematosus and inflammatory bowel disease [ 17 , 18 ]. That might be why the effect of the CD30 expression is more obvious among studies included participants predominant in the early stage.…”
Section: Discussionsupporting
confidence: 81%
“…Next, we also performed triple-IHC for CD30L, since its expression by MCs is up-regulated under pro-inflammatory conditions [86][88]; moreover, activated CD8+ T-cells can express CD30 which is implicated in the control of CD8+ T-cell proliferation and cytokine production [83], [85], [89][91]. Figure 4M–S shows that the total number and percentage of CD30L+ MCs was significantly up-regulated in lesional AA skin compared to healthy and non-lesional human skin ( Figure 4Q,S ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the reason and mechanism of the local anaphylaxis we observed are unclear as of now, Maus and colleagues first reported clinical anaphylaxis resulting from CAR-modified T cells and suggested that anaphylaxis was most likely triggered by an IgE antibody specific for the murine-based antibody sequences present in the CAR-modified T-cell product (16). As the expression of CD30 in normal tissues identified a rare population of large lymphoid cells in sections of lymph node, tonsil, thymus, and endometrial cells with decidual changes (4,17,18), it may be one interpretation of CART-30 cell therapy without significant on-target, off-tumor toxicities.…”
Section: Discussionmentioning
confidence: 99%